1996
DOI: 10.1111/j.1553-2712.1996.tb03365.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Morphine for Early Pain Relief in Patients with Acute Abdominal Pain

Abstract: When compared with saline placebo, the administration of MS to patients with acute abdominal pain effectively relieved pain and did not alter the ability of physicians to accurately evaluate and treat patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(78 citation statements)
references
References 13 publications
1
71
1
5
Order By: Relevance
“…38 Still, we believe that 14% remains unacceptably high; ample evidence currently supports the pre-diagnostic administration of analgesia. 13,14,[39][40][41][42][43][44][45][46] Furthermore, although the proportion of respondents withholding analgesia due to the belief it may mask a surgical diagnosis is significantly lower than reported in other studies, it still portends a delayed approach to providing analgesia in children with abdominal pain and emphasizes the need for wider knowledge translation. Although the majority of respondents indicated they would provide analgesia in an appendicitis scenario (and AAP recommends to provide systemic opioids for severe pain 40 ), less than two-thirds of survey respondents reported a willingness to provide intravenous opioids, despite a pain score of 8 out of 10.…”
Section: Discussionmentioning
confidence: 99%
“…38 Still, we believe that 14% remains unacceptably high; ample evidence currently supports the pre-diagnostic administration of analgesia. 13,14,[39][40][41][42][43][44][45][46] Furthermore, although the proportion of respondents withholding analgesia due to the belief it may mask a surgical diagnosis is significantly lower than reported in other studies, it still portends a delayed approach to providing analgesia in children with abdominal pain and emphasizes the need for wider knowledge translation. Although the majority of respondents indicated they would provide analgesia in an appendicitis scenario (and AAP recommends to provide systemic opioids for severe pain 40 ), less than two-thirds of survey respondents reported a willingness to provide intravenous opioids, despite a pain score of 8 out of 10.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Pace and Burke [9] conducted the first randomized double-blind controlled trial with adequate allocation concealment in ED patients with acute abdominal pain in 1996 and concluded that morphine did not lead to any diagnostic error or physical examination alteration. Contrary to these results, physical examination findings changed in the present study, but did not lead to any diagnostic error.…”
Section: Discussionmentioning
confidence: 99%
“…This belief has been refuted by several studies, which show that diagnostic accuracy is the same [1][2][3] or better 4 in patients who receive opioid analgesia.…”
Section: Introductionmentioning
confidence: 86%